Adsorption behavior of methylene blue dye onto surface modified Strychnos potatorum seeds. Issue 3 (26th June 2012) - Senthamarai, C.; Kumar, P. Senthil; Priyadharshini, M.; Vijayalakshmi, P.; Kumar, V. Vinoth; Baskaralingam, P.; Thiruvengadaravi, K.V.; Sivanesan, S.
<x xml:space="preserve">Abstract</x> Kinetic, mechanism, equilibrium, and thermodynamic behavior of adsorption of methylene blue (MB) dye onto surface modified Strychnos potatorum seeds (SMSP), in an aqueous solution were studied. Batch adsorption experiments were carried out to analyze the effect of initial solution pH, adsorbent dose, contact time, initial MB dye concentration, and temperature on the removal of MB dye. The kinetics of MB dye adsorption onto SMSP follows a pseudo‐second order kinetic model. The adsorption of MB dye onto SMSP was found to be controlled by both surface diffusion and pore diffusion. The diffusivity values were calculated from Boyd kinetic and Shrinking Core Model for varying initial MB dye concentration from 50 to 250 mg L−1. The adsorption equilibrium data were fitted to different adsorption isotherm models such as Langmuir, Freundlich, and Dubinin‐Radushkevich. The equilibrium data fitted best with the Freundlich adsorption isotherm model, which indicates multilayer adsorption of MB dye onto SMSP. The maximum monolayer adsorption capacity estimated with Langmuir isotherm model was 78.84 mg of MB dye molecules per gram of SMSP. Thermodynamic studies showed that the adsorption of MB dye onto SMSP follows an exothermic process. © 2012 American Institute of Chemical Engineers Environ Prog, 32: 624–632, 2013